Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan - Servina Rahayu; Nasya Wahyuni; Leni Shofiyani; Ahmad Wahyudi Zein (CV. ITTC INDONESIA, 2025)
Good Corporate Governance (GCG) is a corporate governance system that plays an important role in creating transparent, accountable, and sustainable corporate management. The implementation of GCG principles is believed to enhance investor confidence and minimize the risks faced by companies, thereby contributing to an increase in firm value. This study employs a qualitative approach using a library research method, conducted through the review of books, academic journals, regulations, and other relevant literature. The findings indicate that the effective implementation of Good Corporate Governance, through the principles of transparency, accountability, responsibility, independence, and fairness, plays a significant role in improving corporate performance and firm value from investors’ perspectives. Therefore, Good Corporate Governance not only functions as a form of regulatory compliance but also serves as a strategic approach for companies in creating long-term value and business sustainability.